A robust eco-compatible microporous iron coordination polymer for CO2 capture. Issue 15 (18th March 2022) - Benzaqui, Marvin; Wahiduzzaman, Mohammad; Zhao, Heng; Hasan, Md Rafiul; Steenhaut, Timothy; Saad, Ali; Marrot, Jérôme; Normand, Périne; Grenèche, Jean-Marc; Heymans, Nicolas; De Weireld, Guy; Tissot, Antoine; et al.
Abstract : A novel and water stable Fe(iii ) based porous coordination polymer was discovered. Due to its interesting features for CO2 capture, this material was used as an inorganic filler for the processing of composite membranes in CO2 /N2 separation. Abstract : Iron(iii ) carboxylate based metal organic frameworks (MOFs)/porous coordination polymers (PCPs) have sparked great interest owing to their high structural diversity and tunable porosity, excellent stability, tailored functionality and their scalability as well as green synthesis associated with their biocompatible and biodegradable character. Herein, we present a new robust Fe(iii ) based PCP (labelled MIL-178(Fe)) built up from chains of corner sharing Fe octahedra interconnected by 1, 2, 4-benzene tricarboxylic acid, delimiting one dimensional narrow pore channels (pore diameter < 4.5 Å) decorated with polar groups (μ2 -OH and –CO2 H functions). These structural and chemical features are suitable for the selective adsorption of CO2 . MIL-178(Fe) was synthesized following a simple and green protocol in water under near ambient conditions using non-toxic reactants, allowing the production of sub-micrometer sized MIL-178(Fe) particles in a large amount (30 g). As shown by single-gas isotherms and CO2 /N2 co-adsorption experiments as well as molecular simulations, this material exhibits a moderate CO2 capacity at low pressure but a high CO2 /N2 selectivity. This is fully consistent with the presence of μ2 -OH groups acting as CO2 adsorption sites, as revealed from both molecular simulations and in situ PXRD experiments. Finally, the good compatibility of this MOF with the elastomer block copolymer Pebax®-3533 allowed the processing of homogeneous and defect-free mixed matrix membranes with a MIL-178(Fe) loading of up to 25 wt% that outperformed pure Pebax®-3533 membranes for CO2 /N2 separation.